Crystal structure of HINT from Helicobacter pylori - Tarique, K. F. (International Union of Crystallography, 2016)

(untitled) (Acta Crystallogr F Struct Biol Commun)
Proteins belonging to the histidine triad (HIT) superfamily bind nucleotides and use the histidine triad motif to carry out dinucleotidyl hydrolase, nucleotidyltransferase and phosphoramidite hydrolase activities. Five different branches of this superfamily are known to exist. Defects in these proteins in humans are linked to many diseases such as ataxia, diseases of RNA metabolism and cell-cycle regulation, and various types of cancer. The histidine triad nucleotide protein (HINT) is nearly identical to proteins that have been classified as protein kinase C-interacting proteins (PKCIs), which also have the ability to bind and inhibit protein kinase C. The structure of HINT, which exists as a homodimer, is highly conserved from humans to bacteria and shares homology with the product of fragile histidine triad protein (FHit), a tumour suppressor gene of this superfamily. Here, the structure of HINT from Helicobacter pylori (HpHINT) in complex with AMP is reported at a resolution of 3 Å. The final model has R and R (free) values of 26 and 28%, respectively, with good electron density. Structural comparison with previously reported homologues and phylogenetic analysis shows H. pylori HINT to be the smallest among them, and suggests that it branched out separately during the course of evolution. Overall, this structure has contributed to a better understanding of this protein across the animal kingdom.